Empowering African-Canadian Career Excellence - Community Economic Development and Employability Corporation (CEDEC) (Collaborative Unity and Existential Responsibility, 2019)
The African-Canadian Career Excellence (ACCE) initiative was developed to address the loss of highly-educated, English-speaking Black youth from the Greater Montreal Area (Quebec, Canada) facing issues of unemployment and underemployment.
Keywords: Official Language Minority Community (OLMC)

African-Canadian Career Excellence : 2015 Employer Survey - Community Economic Development and Employability Corporation (CEDEC) (2015)
This report provides the final data analysis and interpretation of the 2015 employer survey on the hiring norms and practices of businesses across various sectors and industries in the Greater Montreal area, with a focus on employers’ attitudes towards the importance of a having a diverse workforce. This study is part of the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal.

African-Canadian Career Excellence : 2014 Student Survey : The Needs and Challenges of Education Black Youth in Obtaining Meaningful and Sustainable Employment - Community Economic Development and Employability Corporation (CEDEC) (2015)

Initiative pour l'excellence de la carrière des Afro-Canadiens : Enquête réalisée en 2014 : Les besoins et les défis auxquels font face les jeunes de race noire pour obtenir un emploi rémunérateur et durable - Community Economic Development and Employability Corporation (CEDEC) (2015)
Ce rapport présente l’analyse et l’interprétation de l’enquête réalisée auprès des étudiants du premier cycle universitaire en 2014 sur leurs perceptions de la transition vers l’emploi à Montréal. Ce résumé, une étape réalisée par l’Initiative pour l’Excellence de la carrière des Afro-Canadiens œuvrant à contrer la migration des jeunes diplômés noir montréalais, vise à influencer la conception de formations s’adressant aux jeunes diplômés afin de faciliter le lancement de leur carrière et la progression de celle-ci au Québec.

African-Canadian Career Excellence : Undergraduate Survey 2011-2012 Summary Report - Community Economic Development and Employability Corporation (CEDEC) (2013)
This summary report provides the final data analysis and interpretation of the 2011-2012 undergraduate student survey on perceptions of transition to employment in Montreal. As one step in the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal, this summary will inform the design of development training for young graduates to facilitate their career launch and advancement in Quebec. Information and insights herein were provided by the following members of ACCE: Dorothy W. Williams of the Black Community Resource Centre (BCRC), Dwight Best of the African and Caribbean Students’ Network of Canada (ACSioN), Tamara Hart of the Tyndale St-Georges Community Centre, Velda Bourne, Karima West, and Nina Kim and Larissa Milo-Dale of the Community Economic Development and Employability Corporation (CEDEC). Preliminary data analysis and interpretation were contributed by Jan Warnke J W COMM INC.

Initiative pour l'excellence de la carrière des Afro-Canadiens : Sondage réalisé auprès des étudiants du premier cycle universitaire - Community Economic Development and Employability Corporation (CEDEC) (2013)
Ce rapport sommaire consigne les résultats et l'interprétation de l'analyse des données du sondage réalisé auprès des étudiants au premier cycle universitaire de 2011-2012 sur leurs perceptions de la transition vers le marché du travail de Montréal. Comme l’une des démarches de l'Initiative pour l’Excellence de la carrière des Afro-Canadiens consiste à contrer la migration des diplômés noirs de Montréal, ce rapport influencera l'élaboration de formations de perfectionnement pour les jeunes diplômés afin de faciliter l’amorce de leur carrière et leur progression professionnelle au Québec.